2007
DOI: 10.1039/b700919d
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in Lake Maggiore (Italy and Switzerland)

Abstract: Samples of air (gas and particulate phases), bulk deposition, aquatic settling material and sediments were collected in Lake Maggiore (LM) in order to determine their content of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs). Air (gas and particulate phases) concentrations were 0.5 pg m(-3), 80 pg m(-3), 13 pg m(-3) and 106 pg m(-3) for SigmaPCDD/Fs, SigmaPCBs, Sigma dioxin-like PCBs (DL-PCBs) and SigmaPBDEs, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 80 publications
7
26
3
2
Order By: Relevance
“…With an exception of BDE-209, the measured S 13 PBDEs were generally similar to those reported for many areas in other countries, like 21, 4.5e65, and 3e30 pg/m 3 in Birmingham, Kyoto, and Toronto, respectively (Harner et al, 2006;Harrad and Hunter, 2006;Hayakawa et al, 2004). For BDE-209, the concentrations in our study were similar to those reported for a number of places including Izmir, Turkey, Chicago, U.S. (Cetin and Odabasi, 2008;Hoh and Hites, 2005), but much higher than those measured in a rural site in the Great Lakes, two urban sites in South East Queensland, Australia, an industrial urban site in Lake Maggiore, Italy, and those found in the atmosphere at a research center in northern Italy (Su et al, 2009;Toms et al, 2009;Vives et al, 2007;Mariani et al, 2008). For all the PBDE congeners including BDE-209, the concentrations in northern China were significantly lower than those found in the Pearl River Delta area of southern China (Chen et al, 2006;Deng et al, 2007).…”
Section: Pbde Concentrations In Ambient Air Of Northern Chinasupporting
confidence: 87%
See 1 more Smart Citation
“…With an exception of BDE-209, the measured S 13 PBDEs were generally similar to those reported for many areas in other countries, like 21, 4.5e65, and 3e30 pg/m 3 in Birmingham, Kyoto, and Toronto, respectively (Harner et al, 2006;Harrad and Hunter, 2006;Hayakawa et al, 2004). For BDE-209, the concentrations in our study were similar to those reported for a number of places including Izmir, Turkey, Chicago, U.S. (Cetin and Odabasi, 2008;Hoh and Hites, 2005), but much higher than those measured in a rural site in the Great Lakes, two urban sites in South East Queensland, Australia, an industrial urban site in Lake Maggiore, Italy, and those found in the atmosphere at a research center in northern Italy (Su et al, 2009;Toms et al, 2009;Vives et al, 2007;Mariani et al, 2008). For all the PBDE congeners including BDE-209, the concentrations in northern China were significantly lower than those found in the Pearl River Delta area of southern China (Chen et al, 2006;Deng et al, 2007).…”
Section: Pbde Concentrations In Ambient Air Of Northern Chinasupporting
confidence: 87%
“…On the other hand, some studies revealed relatively small fraction of BDE-209. For instance, the dominant congener found in the atmosphere at a research center in northern Italy and in Lake Maggiore, Italy was BDE-47 (Mariani et al, 2008;Vives et al, 2007). The research conducted in a Mediterranean coastal site, France, found that BDE-47 (45 AE 0.5%) and BDE-99 (39 AE 0.2%) predominated in the total PBDEs (Castro-Jiménez et al, 2011).…”
Section: Pbde Congener Profilesmentioning
confidence: 99%
“…Extremely high values were observed in the sites S12 (61,500 ng g −1 ) in Yangtze River Delta, S22 (559 ng g −1 ) and S23 (141 ng g −1 ) in Pearl River Basin. These results were higher than those observed in Lake Maggiore in Europe (0.06-27 ng g −1 dw, Vives et al, 2007) and Great Lake area (Song et al, 2005a(Song et al, , 2005b(Song et al, , 2004. PBDE levels were relatively higher than the other two contaminants in Yangtze River Delta, Pearl River Basin and Haihe River Basin, where the developed industries and commerce were more aggregated.…”
Section: The Overall Concentrations and Distributioncontrasting
confidence: 47%
“…The levels were in the same range with data from the Napoleon Gulf and Thurston Bay of Lake Victoria (Ssebugere et al, 2013b) and other fresh water bodies in Africa like the Nile River in Egypt (El-Kady et al, 2007), Vaal River in South Africa (Nieuwoudt et al, 2009) and Lake Awassa in Ethiopia (Urbaniak and Zalewski, 2011) (Table 2). The levels were low to moderate compared to the data reported in sediments from industrialized areas in the United States of America (Kannan et al, 2008;Loganathan et al, 2008;Shen et al, 2009;Yunuén et al, 2011) and Europe (Nunes et al, 2011;Vives et al, 2007). The results were lower than those reported in sediments from Asia: Can Gio in Vietnam and Japan (Kishida et al, 2010); Xiangjiang River in China (Chen et al, 2012) and Lake Shihwa in Korea (Moon et al, 2012).…”
Section: Concentrations Of Pcdd/fs In the Sedimentscontrasting
confidence: 58%